ESTRATÉGIAS PARA A REDUÇÃO DE ERROS DE MEDICAÇÃO DURANTE A HOSPITALIZAÇÃO: REVISÃO INTEGRATIVA - Claudia Regina de Barros Costa; Sara Soares dos Santos; Simone de Godoy; Leila Maria Marchi Alves; Ítalo Rodolfo Silva; Isabel Amélia Costa Mendes (Universidade Federal do Paraná, 2021)
Objective: to synthesize the knowledge related to strategies to reduce medication errors during the hospitalization of adult patients. Method: integrative literature review carried out in October 2020 through the search for publications in electronic databases: Web of Science, Pubmed, Cumulative Index of Nursing and Allied Health Literature, Latin American and Caribbean literature in Health Sciences and Google Scholar. Results: sample composed of 12 studies, whose strategies for the reduction of medication errors were presented according to the categories: involvement of the clinical pharmacist in clinical activities, implementation of information technologies, educational strategies mediated by simulation and games, and workload reduction. Conclusion: associated with technologies, the involvement of the clinical pharmacist in the medical and nursing team will result in improvements in the reduction of adverse medication events and in the quality of care provided to the patient.